The ethics of generative artificial intelligence in education under debate. A perspective from the development of a theoretical-practical case study - Francisco José García-Peñalvo; María José Casañ-Guerrero; Marc Alier-Forment; Juan Antonio Pereira-Varela (Revista Española de Pedagogía, 2025)
This article examines the ethics of generative artificial intelligence (GenAI) in higher education from a theoretical and practical perspective. It reflects the growing importance of teaching ethics in information technology and its impact on society. Its aim is to develop a training model integrates ethical reflection on GenAI into the education of computer engineering students. To achieve this, a case study is used based on the Social and Environmental Aspects of Computer Science module at the Universidad Politécnica de Cataluña, in which the theoretical principles of artificial intelligence (AI) ethics are applied through a case study of the use of GenAI within the course. Several examples of GenAI systems within AI applied to education are introduced. One of the examples, developed by the authors, involves an AI assistant built using the LAMB framework that enables students to analyse the proposed case using the PESTLE (political, economic, social, technological, legal, and environmental) method with the assistant acting as an expert. Students are then required to analyse a similar case study in another domain. The results suggest that this theoretical-practical approach, where abstract concepts of AI ethics and safety are grounded in specific decisions about application and concrete technological artefacts, effectively integrates ethical reflection into engineering education, highlighting the need for multidisciplinary approaches to address emerging ethical challenges in AI and education.